2014
DOI: 10.3855/jidc.4255
|View full text |Cite
|
Sign up to set email alerts
|

Canine giardiosis in Sardinia Island, Italy: prevalence, molecular characterization, and risk factors

Abstract: Introduction: The flagellate protozoan Giardia duodenalis causes infection in humans and in various animals. Eight distinct assemblages (A-H) have been identified within G. duodenalis; assemblages A and B are those specific to humans and animals, and assemblages C to H are restricted to animal hosts. Methodology: The present study estimated the prevalence of G. duodenalis assemblages in dogs living in the Sardinia region and evaluated the related risk factors. Individual fecal samples were collected from 655 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
4
20
3
Order By: Relevance
“…Statistical analysis indicated that the prevalence of Giardia significantly decreased with increasing of the age of animals, they were detected in dogs aged >12 months in a limited number (6/136). In concordance, previous studies [ 8 , 15 , 25 ] showed a strong correlation between the age and presence of Giardia cysts in stool samples. The same tendency was also observed in Giardia infected cats by Itoh et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Statistical analysis indicated that the prevalence of Giardia significantly decreased with increasing of the age of animals, they were detected in dogs aged >12 months in a limited number (6/136). In concordance, previous studies [ 8 , 15 , 25 ] showed a strong correlation between the age and presence of Giardia cysts in stool samples. The same tendency was also observed in Giardia infected cats by Itoh et al .…”
Section: Discussionsupporting
confidence: 92%
“…[ 6 ] in Japan. This might be linked to the possibility of frequent exposure of old animals to infection which might provide some sort of protection [ 15 ]. Thus, separating the dogs <12 months of age from older animals might be an effective way to reduce exposure to Giardia parasite within the dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Because none of the G. duodenalis isolates obtained from pet dogs in the present survey could be genotyped at the assemblage level, more research should be conducted to elucidate the actual role of domestic dogs as natural reservoirs of human giardiosis. Finally, hunting dogs exhibited the lowest (20.6%) G. duodenalis infection rate, a figure in the lower range of those (20–30%) reported in similar studies conducted in Spain [ 19 ] and Italy [ 37 ].…”
Section: Discussionmentioning
confidence: 67%
“…Sheltered and breeding dogs had a significantly higher prevalence compared to hunting dogs, but not compared to other dog categories. Kennel dogs have been demonstrated to be at higher risk of infection due to continuous exposure to G. duodenalis cysts in kennels with high animal density [ 6 , 8 , 37 ]. Of interest was also the high (35.7%) prevalence of G. duodenalis observed in pet dogs, a potentially serious public health concern if infected animals are in close contact with children or immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Grass and sand substrates provide favourable conditions for the survival and development of the infective stages of the Giardia species 18. Puppies are more susceptible to infection than adult dogs, and immune-competent dogs act as carriers without showing overt clinical signs 20 21. In some development stages, the Giardia species attaches to the surface of enterocytes in the small intestine, resulting in maldigestion, malabsorption and diarrhoea.…”
Section: Discussionmentioning
confidence: 99%